Risk-based management of occupational safety and health in the construction industry – Part 2: Quantitative model. (April 2015) - Sousa, Vitor; Almeida, Nuno M.; Dias, Luís A.
Highlights: Safety and Health Potential Risk Model. Monte Carlo Simulation. U.S. construction industry and subsectors. Fatal accidents costs per man.hour. Abstract: During the last decades, there has been a growing awareness about occupational safety and health risks by the various interested parties in the construction industry. However, despite the substantial improvements achieved, the rate of accidents is still significantly higher than in most of the other industries. Two major reasons have been used to explain this high rate of accidents in the construction industry: (i) the intrinsic riskiness due to the nature of the activities and the particular characteristics of constructions projects and organizations; and (ii) the financial and economic issues regarding the implementation of additional safety measures in a growing competitive market. This companion paper is presented in two parts. The present document refers to Part 2 and makes use of the background knowledge and existing initiatives reviewed in Part 1 to propose and detail the Occupational Safety and Health Potential Risk Model (OSH-PRM). The proposed model was conceived to assist in conducting cost-benefit analysis for occupational safety and health risk management. The OSH-PRM enables an enhanced management of the resources available to improve safety and health conditions in the various activities and for different groups of workers involved in the execution stage of a construction project.